An investigation of a neuro-inflammatory profile of HIV-associated neurocognitive disorders - Williams, Monray Edward (Department of Psychiatry and Mental Health, 2021)
Background HIV-associated neurocognitive disorder (HAND) is the consequence of the effects of HIV-1 within the central nervous system (CNS). HIV-associated neurocognitive impairment differs in severity with milder forms presenting in 50% of people living with HIV (PLWH), regardless of treatment status. Chronic immune dysregulation has been associated with HAND; in particular, it has been noted that inflammation persists despite the successful treatment with antiretroviral therapy (ART). However, the nature to which (neuro)inflammation influences cognitive performance and brain integrity remain unclear. Further, it is not clear how sequence variation in neurotoxic viral proteins, including Tat, affects inflammation in PLWH. This study aimed to 1) perform a systematic review of the existing literature to identify changes in peripheral immune markers that are associated with HAND in ART-experienced PLWH, 2) determine the association of blood peripheral immune markers with domain-based neurocognitive performance and structural brain changes in South African PLWH, and 3) lastly, to evaluate the possible influence of Tat sequence variation on a dysregulated immune profile in HIV-1C infection (i.e. Tat-C). Methods A systematic review of the published literature was performed to identify the most common markers associated with HAND in the ART-era. A panel of markers was measured in a treatment naïve South African cohort by enzyme-linked immunosorbent assays (ELISA). Cognitive performance was established using a battery of tests sensitive to HIV-associated neurocognitive impairment, with domain based scores utilized in analysis. Thickness and surface area of all cortical regions were derived using automated parcellation of T1-weighted images acquired at 3T. Markers were correlated with neurocognitive performance and cortical thickness and surface area. Further, a prospective review of the literature was performed to determine the association between Tat sequence variation and underlying mechanisms (and inflammation) of HAND. The HIV-1 was genotyped and the influence of Tat sequence variation on immune marker levels was evaluated in a subset of South African participants. Results A systematic review of the existing literature suggested that peripheral immune markers of monocyte activation (sCD14 and sCD163) and inflammation (IL-18 and IP10) were associated with HAND in the majority of studies. Evaluation of blood immune markers in a treatment naïve South African cohort showed that thymidine phosphorylase (TYMP) and neutrophil gelatinase-associated lipocalin (NGAL) levels were significantly higher, while matrix metalloproteinase (MMP)9 levels were significantly lower in PLWH. The results further showed that in PLWH, worse psychomotor processing speed was associated with higher TYMP and NGAL levels and worse motor function was associated with higher NGAL levels. Further, in imaging analysis, it was reported that higher NGAL levels were associated with the reduced thickness of the bilateral orbitofrontal cortex. The association of NGAL withworse motor function was mediated by the cortical thickness of the bilateral orbitofrontal cortex. The associations between higher NGAL and TYMP levels with cortical thickness were largely found in the regions of the frontal cortex. A review of the literature suggests that key protein signatures (C31S and R57S) present in the Tat protein from HIV-1 subtype C (Tat-C) infection may contribute to the lowered inflammation. Supporting this hypothesis, the results from this thesis showed that HIV-1C participants with the R57S mutation had lower peripheral TYMP levels. Conclusions Current literature supports the premise that chronic inflammation may be an important contributor to the development of the milder forms of HAND. For patients on ART, other strategies are required to address the ongoing peripheral inflammation, in addition to simply suppressing the viral load. In a South African context, TYMP and NGAL may be promising markers for their involvement in HAND. Patients were largely treatment-naïve; therefore, these markers may represent HIV related effects without the potential confounding effects of ART. Therefore, these findings may represent long-standing effects which might persist in treatment experienced participants. In HIV-1C infection, the level of certain inflammatory markers may be influenced by the R57S Tat protein signature. To our best knowledge, this is the first thesis to report the association of these markers with HAND. These immune markers need to be investigated for their potential role in the underlying mechanisms of HAND.